Effect of Substrate Concentration on the Amylase Activity in Germinating Buckwheat Seeds - Deshwal Sapna (International Journal of Research in Chemistry and Environment (IJRCE), 2011)
Common Buckwheat ( Fagopyrum esculentum Moench) seeds were taken and germinated in dark at room temperature. Dialysis was used for the partial purification of amylases and then, the effect of substrate concentration on amylases was determined. The Km of amylases was 9mg starch and Vmax was 14.30 µ moles of maltose per 30 min. In conclusion, the amylases from the Buckwheat showed high level of activity during seed germination, has low Km and low Vmax. These characterization meets the prerequisite needs of the food industry and useful in the malting of Buckwheat seed for the production of various products.